Proxy markers of serum retinol concentration, used alone and in combination, to assess population vitamin A status in Kenyan children: a cross-sectional study - Talsma, E.F.; Verhoef, H.; Brouwer, Inge D.; Mburu-de Wagt, A.S.; Hulshof, P.J.M.; Melse-Boonstra, A. (Springer, 2015)
Background: Serum retinol concentration determined by high-performance liquid chromatography (HPLC) is recommended by the World Health Organization to assess population vitamin A status. This assay is expensive, technically demanding and rarely available in developing countries. Our objective was a) to assess the diagnostic performance of proxy markers in detecting vitamin A deficiency and b) to derive decision rules based on these markers to estimate vitamin A deficiency prevalence.